2019
DOI: 10.3390/f10121102
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Paraffin-Thermal Modification of Beech Wood on Its Biological, Physical and Mechanical Properties

Abstract: The European beech (Fagus sylvatica L.) wood was thermally modified in the presence of paraffin at the temperatures of 190 or 210 °C for 1, 2, 3 or 4 h. A significant increase in its resistance to the brown-rot fungus Poria placenta (by 71.4%–98.4%) and the white-rot fungus Trametes versicolor (by 50.1%–99.5%) was observed as a result of all modification modes. However, an increase in the resistance of beech wood surfaces to the mold Aspergillus niger was achieved only under more severe modification regimes ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
0
10
1
Order By: Relevance
“…In this experiment, in contrast to the experiment with the paraffin-thermally modified beech wood (Reinprecht and Repák 2019), the white-rot fungus T. versicolor did not cause higher weight losses of the PEG-thermally modified beech wood than the brownrot fungus P. placenta. However, comparing with the paraffin-thermally modified beech wood, when its resistance to rot increased always on the 99.9% significance level (Reinprecht and Repák 2019), the anti-rot effect of the PEG-thermal modification modes was clearly lower (Table 1). This could also be caused by a washout of water soluble PEG macromolecules from modified wood during the mycological testso an initial water washout of specimens by EN 84 (1997) would be appropriate.…”
Section: Resistance Of the Peg-thermally Treated Beech Wood To Decayi...contrasting
confidence: 74%
See 4 more Smart Citations
“…In this experiment, in contrast to the experiment with the paraffin-thermally modified beech wood (Reinprecht and Repák 2019), the white-rot fungus T. versicolor did not cause higher weight losses of the PEG-thermally modified beech wood than the brownrot fungus P. placenta. However, comparing with the paraffin-thermally modified beech wood, when its resistance to rot increased always on the 99.9% significance level (Reinprecht and Repák 2019), the anti-rot effect of the PEG-thermal modification modes was clearly lower (Table 1). This could also be caused by a washout of water soluble PEG macromolecules from modified wood during the mycological testso an initial water washout of specimens by EN 84 (1997) would be appropriate.…”
Section: Resistance Of the Peg-thermally Treated Beech Wood To Decayi...contrasting
confidence: 74%
“…Comparing analogous methods of wood thermall modification in melts, i.e., the paraffin-thermal method (Reinprecht and Repák 2019) and the PEG-thermal method present in this work, it can be concluded that PEG 6000 has a lower inhibitory effect against rot by decaying fungi compared to paraffin. This can be attributed mainly to the hydrophilic nature of PEG.…”
Section: Resistance Of the Peg-thermally Treated Beech Wood To Decayi...mentioning
confidence: 74%
See 3 more Smart Citations